Striking a bargain: Narrative identification of wage bargaining shocks - Žymantas Budrys; Mario Porqueddu; Andrej Sokol (European Central Bank (ECB), 2021)
We quantify the effects of wage bargaining shocks on macroeconomic aggregates using a structural vector auto-regression model for Germany. We identify exogenous variation in bargaining power from episodes of minimum wage introduction and industrial disputes. This narrative information disciplines the impulse responses to a wage bargaining shock of unemployment and output, and sharpens inference on the behaviour of other variables. The implied transmission mechanism is in line with the theoretical predictions of a large class of search and matching models. We also find that wage bargaining shocks explain a sizeable share of aggregate uctuations in unemployment and in ation, that their pass-through to prices is very close to being full, and that they imply plausible dynamics for the vacancy rate, firms' profits, and the labour share.
Keywords: J2; J3; E32; C32; 330; Wage bargaining; minimum wage; industrial action; narrative restrictions; structural vector autoregression